Leitura literária em signwriting: metodologias docentes para a formação do leitor surdo - Gumiero, Daniela Gomes (2020)
This research aims to learn about different methodologies of literary reading in SignWriting used by teachers for deaf students of basic education. In this perspective, we will seek practices with this writing system at higher levels than that of literacy, enhancing the training and not the "formatting" of the deaf reader. The theoretical reference on literature and specificities comes from reflections by authors such as Mortatti, Zilberman, Abramovich, Colomer, Chartier, Bakhtin as well as by authors of the Brazilian Sign Language – Libras and SignWriting, being Barreto, Karnopp, Strobel, Gesser. It adopts bibliographic-documental type and field research. From the observations, it appears that the teachers use different methods in the work with literary reading in SignWriting as free, individual, collective, mediated reading, use printed material, digital, signaled form. As for the students, they actively participate in the reading process, position themselves, express interest and curiosity. We found that the methodological practices worked by the teachers offer reading for pleasure and sensitivity, fleeing from reading due to obligation, which significantly contributes to the development and reading training of these students.